Empowerment of The Madrasah in Fulfillment of Children's Rights to Education (CRE) Through Assistance Child-Friendly School in Madrasah and Raudhatul Athfal - Riswani Riswani; Nurhasanah Bakhtiar; Nurkamelia Mukhtar AH; Heldanita Heldanita (Murhum : Jurnal Pendidikan Anak Usia Dini, 2023)
The policy of child-friendly schools (CFS) is the government's effort to fulfill the right to education for children However, this policy has not been fully adopted by the madrasah and Raudhatul Athfal (RA). This article discusses what programs can increase motivation and improve understanding of child-friendly school management in madrasah and RA. The community service uses the Asset Based Community Development (ABCD) approach refer to John McKnight and Jody Kretzmann (1993) and Bandura social learning theory. The results of the service show that the CFS socialization program through web seminar has increased the madrasah's understanding of the concept of CFS and motivated the madrasah to adopt CFS. The results also showed that the program socialization for CFS standards and training on children's rights conventions increased the understanding of madrasahand RA in managing CFS. The community service recommends the next community service involve the madrasah committees and community